FEEDBACK INDEX The Theory of HR Quantification - Jain, Pooja; Jain, Pranjal (International Journal of Psychosocial Rehabilitation, 2020)
This research introduces the concept of Feedback Index (FI) as a subset of Theory of HR Quantification. It is a mathematical tool which states how much value does an organization accords to the concept of feedback in quantitative terms. Organizations having higher Feedback Index tend to have higher employee engagement and enhanced employee satisfaction which drives the organizational productivity. Two types of FI have been devised: Organizational Feedback Index (OFI) and Employee Feedback Index (EFI). OFI which is the topic of interest for the present study acts as a measurement of the amount of employee empowerment. FI has a vast scope of applications and it is set to become the next parameter for ranking organizations.